Evaluate the effectiveness of internal control systems and their role in providing an effective governance framework in Sudanese banks - ابراهيم محي الدين محمد; اسماعيل ابراهيم يعقوب; محمد صديق ادم (Journal of Economics and Administrative Sciences, 2019)
The study aimed to find out the relationship between the dimensions of internal control systems and the availability of an effective governance framework in the Sudanese banks. The study used descriptive and analytical method for collecting and analyzing the study data using SPSS program. The questionnaire was used as an analysis tool. The target sample of Sudanese bank employees, the study found several results, including that the bank avoids methods that lead to the rational use of available resources, and identifies and separation of tasks among employees, in addition to rapid response to reports The study found several recommendations, including the need for a list of banks that are sufficiently flexible and compatible with the needs of customers, in addition to the foundations for the follow-up and accountability of banks’ employees..